Shape-adaptive single-molecule magnetism and hysteresis up to 14 K in oxide clusterfullerenes Dy2O@C72 and Dy2O@C74 with fused pentagon pairs and flexible Dy–(μ2-O)–Dy angle. Issue 18 (28th April 2020) - Velkos, Georgios; Yang, Wei; Yao, Yang-Rong; Sudarkova, Svetlana M.; Liu, XinYe; Büchner, Bernd; Avdoshenko, Stanislav M.; Chen, Ning; Popov, Alexey A.
Abstract : Clusterfullerenes Dy2 O@C72 and Dy2 O@C74 demonstrate a fine balance of exchange and dipolar interactions and slow relaxation of magnetization. Abstract : Dysprosium oxide clusterfullerenes Dy2 O@Cs (10528)–C72 and Dy2 O@C2 (13333)–C74 are synthesized and characterized by single-crystal X-ray diffraction. Carbon cages of both molecules feature two adjacent pentagon pairs. These pentalene units determine positions of endohedral Dy ions hence the shape of the Dy2 O cluster, which is bent in Dy2 O@C72 but linear in Dy2 O@C74 . Both compounds show slow relaxation of magnetization and magnetic hysteresis. Nearly complete cancelation of ferromagnetic dipolar and antiferromagnetic exchange Dy⋯Dy interactions leads to unusual magnetic properties. Dy2 O@C74 exhibits zero-field quantum tunneling of magnetization and magnetic hysteresis up to 14 K, the highest temperature among Dy-clusterfullerenes.